Early ERP Signature of Hearing Impairment in Visual Rhyme Judgment - Classon, Elisabet; Rudner, Mary; Johansson, Mikael; Rönnberg, Jerker (Frontiers in Psychology, 2013)
Postlingually acquired hearing impairment is associated with changes in the representation of sound in semantic long-term memory. An indication of this is the lower performance on visual rhyme judgment tasks in conditions where phonological and orthographic cues mismatch, requiring high reliance on phonological representations. In this study, event-related potentials (ERPs) were used for the first time to investigate the neural correlates of phonological processing in visual rhyme judgments in participants with acquired hearing impairment (HI) and normal hearing (NH). Rhyme task word pairs rhymed or not and had matching or mismatching orthography. In addition, the interstimulus-interval (ISI) was manipulated to be either long (800 ms) or short (50 ms). Long ISIs allow for engagement of explicit, top-down processes, while short ISIs limit the involvement of such mechanisms. We hypothesized lower behavioural performance and N400 and N2 deviations in HI in the mismatching rhyme judgment conditions, particularly in short ISI. However, the results showed a different pattern. As expected, behavioural performance in the mismatch conditions was lower in HI than in NH in short ISI, but ERPs did not differ across groups. In contrast, HI performed on a par with NH in long ISI. Further, HI, but not NH, showed an amplified N2-like response in the non-rhyming, orthographically mismatching condition in long ISI. This was also the rhyme condition in which participants in both groups benefited the most from the possibility to engage top-down processes afforded with the longer ISI. Taken together, these results indicate an early ERP signature of hearing impairment in this challenging phonological task, likely reflecting use of a compensatory strategy. This strategy is suggested to involve increased reliance on explicit mechanisms such as articulatory recoding and grapheme-to-phoneme conversion.